Bio-efficacy of some early post-emergence herbicides in soybean (Glycine max L.) - Mishra, Pratiksha; Singh, Harvir; Babu, Subhash; Pal, Suresh (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season of 2011 at Breeder Seed Production Unit of Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (M.P.) to test the bio-efficacy of early post-emergence herbicides against associated weeds in soybean (Glycine max L.). Eleven weed control treatments viz T1 [Odyssey (imazethapyr 35% + imazamox 35%) active ingredient (@) 52.5 and dose 75 g ai/ha], T2 [Odyssey active @61.25 and 87.5 g ai/ha], T3 [Odyssey @ 70 and 100 g ai/ha], T4 [Odyssey @ 52.5 and 75 g ai/ha+1000 ml adjuvant], T5 [Odyssey @ 61.25 and 87.5 g ai/ha+1000 ml adjuvant], T6 [Odyssey @ 70 and 100 g ai/ha+1000 ml adjuvant], T7 [Imazethapyr @ 100 and 1000ml ai +1000ml adjuvant], T8 [Imazamox @42 and 350ml ai+1000 ml adjuvant], T9 [Chlorimuron ethyl @ 9.37 and 37.5 g ai/ha], T10 [Fenoxoprop-ethyl @ 67.5 and 750 ml ai], T11 [weedy check], were laid out in a randomized block design with three replications. Among the herbicide treatments, odyssey applied between 75g and 100 g/ha with 1000 ml adjuvant/ha as early post-emergence, controlled most of the weed flora and significantly recorded the weed biomass and improve the weed control index as compared to weedy check. Odyssey (common name) is the ready mixture of imazethapyr 35% + imazamox 35% and applied as early post- emergence. Application of odyssey between 75g and 100 g /ha as early post-emergence and found superior over other treatments. Recorded higher value of yield attributes (pods/plant, seeds/pod, seed index), grain and straw yields and gross return net return and B:C ratio, followed by T5 (Odyssey + Adjuvant 87.5 g + 2 ml).